" Impact of Transformational leadership in the organizational performance - Asst. Lecture. Ghassan Abdul Jalil Hamid, Asst. Lecture. Ghassan Abdul Jalil Hamid (The Gulf Economist, 2024)
Abstract : This study aims to determine the extent of the impact of transformational leadership with its five variables on organizational performance in the workplace. The hypothetical plan of the study was built on two variables. This study was tested in the government industrial sector in Iraq. The questionnaire was used as a tool for collecting data in four departments for a sample of (155) employees in the government industrial sector. A set of statistical tools found in AMOS programs were used. V. 24)-SPSS. V. 24) on the stratified sample، This study reached the following conclusions: There is an overall positive effect of transformational leadership (especially vision, supportive leadership, and personal recognition) on organizational performance.